Host–rabies virus protein–protein interactions as druggable antiviral targets - Lingappa, Usha F. (National Academy of Sciences, 2013)
We present an unconventional approach to antiviral drug discovery, which is used to identify potent small molecules against rabies virus. First, we conceptualized viral capsid assembly as occurring via a host-catalyzed biochemical pathway, in contrast to the classical view of capsid formation by self-assembly. This suggested opportunities for antiviral intervention by targeting previously unappreciated catalytic host proteins, which were pursued. Second, we hypothesized these host proteins to be components of heterogeneous, labile, and dynamic multi-subunit assembly machines, not easily isolated by specific target protein-focused methods. This suggested the need to identify active compounds before knowing the precise protein target. A cell-free translation-based small molecule screen was established to recreate the hypothesized interactions involving newly synthesized capsid proteins as host assembly machine substrates. Hits from the screen were validated by efficacy against infectious rabies virus in mammalian cell culture. Used as affinity ligands, advanced analogs were shown to bind a set of proteins that effectively reconstituted drug sensitivity in the cell-free screen and included a small but discrete subfraction of cellular ATP-binding cassette family E1 (ABCE1), a host protein previously found essential for HIV capsid formation. Taken together, these studies advance an alternate view of capsid formation (as a host-catalyzed biochemical pathway), a different paradigm for drug discovery (whole pathway screening without knowledge of the target), and suggest the existence of labile assembly machines that can be rendered accessible as next-generation drug targets by the means described.